Natural bioactive products in the regulation of bone metabolism and regeneration - Ouyang, Xinyi; Ma, Qiang; Zhou, Chang; Tang, Jiaqian; Li, Mengyuan; Qing, Jun; Lei, Xiaoming; Huang, Dan; Liu, Huiping; Zhang, Guomin (Frontiers in Pharmacology, 2025)
Osteoporosis (OP) is a systemic skeletal disorder characterized by decreased bone mineral density (BMD), impaired bone microarchitecture, and an elevated risk of fragility fractures. Although conventional pharmacological agents—such as bisphosphonates, selective estrogen receptor modulators, and monoclonal antibodies—can attenuate disease progression, their long-term application is limited by adverse effects and suboptimal patient adherence. Consequently, there is growing interest in the development of safer, multi-targeted therapeutic strategies. Plant-derived bioactive products have garnered increasing attention due to their broad pharmacological profiles, including the promotion of osteoblastogenesis, suppression of osteoclastogenesis, regulation of bone–vascular coupling, and modulation of immune and oxidative stress pathways. Recent advances in biomaterial-assisted delivery systems have further improved the physicochemical stability, bioavailability, and tissue-specific delivery of these phytochemicals, thereby enhancing their therapeutic efficacy in bone regeneration. Although accumulated in vitro and in vivo studies suggest the bone-protective potential of these natural agents, clinical translation remains limited. Further mechanistic investigations and rigorously designed clinical trials are warranted to substantiate their efficacy and safety in human populations. This review summarizes recent progress in the mechanistic understanding of natural products involved in bone metabolism, with a particular focus on representative classes such as flavonoids, polyphenols, polysaccharides, glycosides, and terpenoids. In addition, we discuss the translational potential of integrating these agents with advanced drug delivery platforms, aiming to provide a theoretical framework and future research directions for the treatment of OP and related bone disorders.